The Hovde Years : A Biography of Frederick L. Hovde - Topping, Robert W. (Book collections on Project MUSE., 2019)
This biography details Hovde’s life and times from his birth at Erie, Pennsylvania, through his boyhood at Devils Lake, North Dakota, and includes his student days at the University of Minnesota and in England and Europe as a Rhodes scholar. In addition, it outlines his career from the time he returned to the United States from England in 1932, as well as when he went back again in 1941 as the United States secretary for American-British scientific research and development exchange efforts. Principally, it covers his twenty-five years as president of Purdue University, his impact on higher education generally, and his retirement in 1971. The book depicts Hovde the president and Hovde the man. It focuses on the growth of Purdue University from the post-World War II years through the tumultuous times of the late 1960s and Hovde’s own comments on those periods.